Patient Preferences and Surrogate Decision Making in Neuroscience Intensive Care Units - Cai, Xuemei (Neurocrit Care, 2015)
In the neuroscience intensive care unit (NICU), most patients lack the capacity to make their own preferences known. This fact leads to situations where surrogate decision makers must fill the role of the patient in terms of making preference-based treatment decisions, oftentimes in challenging situations where prognosis is uncertain. The neurointensivist has a large responsibility and role to play in this shared decision making process. This review covers how NICU patient preferences are determined through existing advance care documentation or surrogate decision makers and how the optimum roles of the physician and surrogate decision maker are addressed. We outline the process of reaching a shared decision between family and care team and describe a practice for conducting optimum family meetings based on studies of ICU families in crisis. We review challenges in the decision making process between surrogate decision makers and medical teams in neurocritical care settings, as well as methods to ameliorate conflicts. Ultimately, the goal of shared decision making is to increase knowledge amongst surrogates and care providers, decrease decisional conflict, promote realistic expectations and preference-centered treatment strategies, and lift the emotional burden on families of neurocritical care patients.